2022
DOI: 10.1289/ehp10343
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evidence Map for Over One Hundred and Fifty Per- and Polyfluoroalkyl Substances (PFAS)

Abstract: Background: Per- and polyfluoroalkyl substances (PFAS) are a large class of synthetic (man-made) chemicals widely used in consumer products and industrial processes. Thousands of distinct PFAS exist in commerce. The 2019 U.S. Environmental Protection Agency (U.S. EPA) Per- and Polyfluoroalkyl Substances (PFAS) Action Plan outlines a multiprogram national research plan to address the challenge of PFAS. One component of this strategy involves the use of systematic evidence map (SEM) approaches to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
65
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 32 publications
1
65
0
2
Order By: Relevance
“…As part of a broader effort to characterize the evidence of health effects associated with exposure to less-studied PFAS, we created a systematic evidence map (SEM) of epidemiology studies of the approximately 150 less-studied PFAS prioritized by the U.S. Environmental Protection Agency (U.S. EPA) for tiered toxicity testing. 11 This SEM is an extension of another recently published SEM of these PFAS, 12 which presented detailed data on animal toxicology studies but only high-level summary study design characteristics (e.g., population, study design, and health effect categories) for epidemiology studies. This SEM uses the same literature search and screen results but adds to the previous analysis with full data extraction and study evaluation of the identified epidemiology studies, allowing the user to access the full quantitative results and risk of bias ratings when examining the available evidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of a broader effort to characterize the evidence of health effects associated with exposure to less-studied PFAS, we created a systematic evidence map (SEM) of epidemiology studies of the approximately 150 less-studied PFAS prioritized by the U.S. Environmental Protection Agency (U.S. EPA) for tiered toxicity testing. 11 This SEM is an extension of another recently published SEM of these PFAS, 12 which presented detailed data on animal toxicology studies but only high-level summary study design characteristics (e.g., population, study design, and health effect categories) for epidemiology studies. This SEM uses the same literature search and screen results but adds to the previous analysis with full data extraction and study evaluation of the identified epidemiology studies, allowing the user to access the full quantitative results and risk of bias ratings when examining the available evidence.…”
Section: Introductionmentioning
confidence: 99%
“…High-level summary information as reported in Carlson et al. 12 is useful at the scoping stage to understand the quantity of available data but does not allow for users to assess the findings or utility of the available studies. The information in this SEM is being disseminated in downloadable formats and an interactive dashboard to facilitate further analyses.…”
Section: Introductionmentioning
confidence: 99%
“…New methods that support improved efficiency and effectiveness of risk assessments, including the systematic evidence map described by Carlson et al. 1 in this issue, are greatly needed.…”
mentioning
confidence: 99%
“…Carlson et al. 1 used machine learning tools to greatly improve the efficiency of the SEM workflow, including SWIFT-Active Screener, which iteratively prioritizes titles and abstracts for manual screening. The use of SWIFT-Active Screener for this purpose has been externally validated.…”
mentioning
confidence: 99%
See 1 more Smart Citation